Investigating Types, Reasons, and Pedagogical Suggestions of Code-Switching in Teacher-Students’ Interaction in EFL Classroom - Thessa Siregar; Syafryadin Syafryadin (JOLLT Journal of Languages and Language Teaching, 2026)
In EFL classrooms, particularly in bilingual contexts such as Indonesia, the use of code-switching has become an inevitable and pedagogically contested practice. While it is often employed to facilitate comprehension and classroom interaction, excessive reliance on code-switching may hinder students’ exposure to the target language and limit their communicative competence development. This research aims to explore the types, reasons, and pedagogical suggestions for implementing code-switching in the classroom by teachers and students. This study employed a qualitative method, including observation and interviews. It involves 5 participants, 1 teacher and 4 students in an English course. The instruments of this study consisted of non-participant classroom observation supported by field notes to capture real-time code-switching occurrences, and semi-structured interviews guided by validated question protocols to explore participants’ underlying reasons and pedagogical suggestions. The findings of the study indicated that teachers and students used inter-switching, intra-switching, and tag- switching. The inter-switching is a dominant switching used. Teachers use code-switching to accommodate the limits of students’ abilities, clarify, emphasize, and explain to ensure they understand the materials and feel comfortable in English learning. On the other hand, the main reasons for students’ lack of vocabulary are difficulty expressing thoughts and low speaking confidence in English. This study highlights suggestions from teachers that the teacher should appropriately select the vocabulary, learning method, and technology implementation for students, maintain confidence, and reduce code-switching in teaching English. The students suggest that they have to practice often and use applications such as Duolingo, Elsa Speak, and YouTube to support their speaking practice, so they can speak English fluently. In conclusion, code switching is a pedagogical and communicative strategy facilitating understanding and interaction in bilingual English classrooms.